Bioethanol production using oil palm trunk sap (opts) by kluyveromyces marxianus - effect of temperature and ph - Siti Norhidayah, Abd Rahman (2014)
This paper presents the kinetic study of bioehanol production using Oil Palm Trunk Sap (OPTS) by Kluyveromyces marxianus. Bioethanol have been discovered as the substitute of petrol that is biodegradable and less toxic than fossil fuels. Oil palm trunk can be used to produce bioethanol from its sap because it contains high glucose and other types of sugars. This study is focus on studying the kinetic parameters of bioethanol production from oil palm trunk sap (OPTS) using Kluyveromyces marxianus. By analyzing specific growth rate, sugar consumption rate and ethanol production rate the kinetic parameters can be determined. The analytical techniques for bioethanol production and substrate consumption were monitored by high-performance liquid chromatography (HPLC) and cell dry weight (CDW) for growth profile. In this study, pH and temperature were varied to study the effect of different pH (3, 4, 5, 6, and 7) and temperature (25ºC, 30ºC, 35ºC, 40ºC, and 45ºC). The highest ethanol concentration was produced at pH 5 which is 26.75 g/L and at temperature 35ºC ethanol concentration production was 45.06 g/L